Internet of things enabled real time cold chain monitoring in a container port - Ahmet Yunus Cil; Dini Abdurahman; Ibrahim Cil (Journal of Shipping and Trade (JST), 2022)
Seaports are regarded as significant actors in global logistics and supply chains since a large part of the cargoes carried over the globe are being processed there. When the cold chain broken down during transport and storage in the ports, the humidity, nutrition, temperature and time conditions to be required for the growth of the bacteria occur, and rapid reproduction occurs and the properties of the products are rapidly deteriorating. It is imperative that especially medicines, some chemical substances and foodstuffs need to be transported without breaking the cold chain in the logistics. The monitoring and control of the temperature and humidity level is important in the time period between the loading of these containers in special areas in ports, the loading of freight in open areas, or the loading of freight on roads and railway carriages. For this reason, precise monitoring and control of the system is vital in the port logistics management.
Keywords: 650; Cold Chain Logistics; Container; Internet of Things; IoT enabled cooling system; Port logistics management; Ports; Remote monitoring and controlling of containers; RFID